Marketing research - Dodge, H. Robert (Ohio : Charles E. Merrill, 1982)
The objective of this basic text in marketing research is to provide students with a learning framework to study the practice of marketing research. By design the text is structured to incorporate the maximum amount of information from actual marketing research. This will give students a sense of the practice of marketing research in addition to an understanding of the field. For example, supplementary readings about practitioners serve as prologues to the chapters. These prologues provide interesting examples from actual experience. In addition, the text includes materials used in practice such as interviewing instructions and descriptions of testing procedures, examples to explain concepts and applications, and cases drawn from actual research projects.
Part I. Developing Research Framework -- Part II. Types of Data -- Part III. Sampling -- Part IV. Data Collection -- Part V. Analysis -- Part VI. Interpretation -- Part VII. Applications of Marketing Research.
Includes index.
Keywords: MARKETING RESEARCH